1981
DOI: 10.1037/0003-066x.36.7.753
|View full text |Cite
|
Sign up to set email alerts
|

Survivors of the Sixties: Comparative psychosocial and political development of former Berkeley student activists.

Abstract: Former Berkeley free speech movement activists were compared with student government contemporaries and a cross section of the 1964-1965 student body along the dimensions of self-and ideal-selfconstructions, locus of control, political beliefs and behavior, occupational choice, and moral development.Though their personality and political activism profiles were not distinctive, former activists were more likely to endorse leftist convictions, to work in human service and creative occupations, to earn lower annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 15 publications
3
58
2
Order By: Relevance
“…Moral judgment and action, therefore, exhibit a monotonic relationship (Blasi 1980(Blasi , 1983. The expectation of a similar link between moral judgment and political activism has guided considerable empirical research (Haan 1975;Keniston 1973;Merelman 1977;Nassi 1981;Weinreich-Haste 1985;Candee 1987) and underlies the use of moral development theory in this study This hypothesis, together with the contention that cognitive theory has cross-cultural validity, support the expectation that moral development significantly affects political activism regardless of ideological affiliation.…”
Section: Abortion Politics and Political Activismsupporting
confidence: 64%
“…Moral judgment and action, therefore, exhibit a monotonic relationship (Blasi 1980(Blasi , 1983. The expectation of a similar link between moral judgment and political activism has guided considerable empirical research (Haan 1975;Keniston 1973;Merelman 1977;Nassi 1981;Weinreich-Haste 1985;Candee 1987) and underlies the use of moral development theory in this study This hypothesis, together with the contention that cognitive theory has cross-cultural validity, support the expectation that moral development significantly affects political activism regardless of ideological affiliation.…”
Section: Abortion Politics and Political Activismsupporting
confidence: 64%
“…In addition, some recent research has also shown that adolescent and adult populations in general manifest the 'higher is better' and 'lower is poorer' syndrome. Nassi (1981) found that adult females at high stages on Kohlberg's moral judgement scoring maintained a commitment to altruistic community activity; those at lower stages did not. Bredemier (1983) found that female athletes at higher stages behaved humanely during competition; those at lower stages did not.…”
Section: Introductionmentioning
confidence: 92%
“…The studies that do exist on this neglected topic typically focus on what the activists do politically. Over time, however, activists gradually move away from collective involvement and movement commitment, although resisting involvement in established institutions (Nassi 1981;Demerath, Marwell, and Aiken 1971;Nassi and Abramowitz 1979;Krauss 1972;Gitlin 1987;Whittier 1995;Whalen and Flacks 1989). Over time, however, activists gradually move away from collective involvement and movement commitment, although resisting involvement in established institutions (Nassi 1981;Demerath, Marwell, and Aiken 1971;Nassi and Abramowitz 1979;Krauss 1972;Gitlin 1987;Whittier 1995;Whalen and Flacks 1989).…”
Section: The State Of Knowledge Activists At the End Of Their Movementmentioning
confidence: 99%
“…Most have found that former activists from the sixties continue to espouse leftist political attitudes (Demerath, Marwell, and Aiken 1971;Fendrich and Tarleau 1973;Maidenberg and Meyer 1970;Whalen and Flacks 1980;Nassi 1981;Fendrich 1974;Fendrich and Lovoy 1988;Fendrich and Krauss 1978;Whittier 1995;McAdam 1988;Whalen and Flacks 1989). Most have found that former activists from the sixties continue to espouse leftist political attitudes (Demerath, Marwell, and Aiken 1971;Fendrich and Tarleau 1973;Maidenberg and Meyer 1970;Whalen and Flacks 1980;Nassi 1981;Fendrich 1974;Fendrich and Lovoy 1988;Fendrich and Krauss 1978;Whittier 1995;McAdam 1988;Whalen and Flacks 1989).…”
Section: The State Of Knowledge Activists At the End Of Their Movementmentioning
confidence: 99%
See 1 more Smart Citation